Significance of social capital in collaborative management of natural resources in Sub-Saharan African rural communities: a qualitative meta-analysis. Issue 3 (2nd September 2017) - Musavengane, Regis; Simatele, Danny
Abstract: Social capital is regarded as a critical asset for attaining common goals that may otherwise be unattainable in community-based schemes. A better understanding of social capital dimensions influencing stakeholder participation in collaborative management of natural resources is vital to help policy-makers design programmes that would be more attractive to participants. This paper explores the role of community participation in natural resources management. It specifically examines the extent to which social capital can be instrumental in enhancing collaborative management of community conservation schemes in Sub-Saharan Africa. We adopted a systematic review of the literature on the role of participation in CBRM, which then forms the basis of a qualitative meta-analysis. The meta-analysis reveals several key social capital variables important for stakeholder participation in community-based resource management schemes including; fairness of rules, dispute resolution procedures, inclusivity, sociability and open dialogue.